ANALYSIS OF PROTECTIVE GAS FLOW AND SEAM FORMATION ON GMAW WELD PROCESS TO HARDNESS AND MICRO STRUCTURE OF ASTM A36 STEEL - Fius Lambang; Mastiadi Tamjidillah (Scientific Journal of Mechanical Engineering Kinematika, 2020)
This study aims to determine the effect of variations in the protective gas flow and seam formation on the hardness and microstructure of ASTM A36 steel. The variation of the protective gas flow used is 5 liters/minute, 10 liters/minute, and 15 liters/minute, while the form of seam used is seam I, ½ V, and V with ER 70S-6 electrodes with a diameter of 1.2 mm. The results showed that the greater protective gas flow would increase the value of violence. The highest increase in weld metal and HAZ hardness was in seam V with 15 liters/minute gas flow as much as 38.06% weld metal, 11.15% HAZ, while the lowest hardness value of weld metal was in gas flow 5 liters/minute at seam ½ V is 41.9 HRB and the lowest HAZ hardness value is in the gas flow of 5 liters/minute in Kampung I which is 40.8 HRB. The highest increase in hardness of base metal was in ½ V with 39.46% with 15 liters/minute gas flow, while the lowest base metal hardness was in Kampung I, 43.4 HRB with 5 liters/minute gas flow. The structural test results show the higher the protective gas flow will increase the formation of more pearlite. The highest percentage of pearlite formation is in the weld metal of seam V, which is 53.16% and the percentage of pearlite at least in the HAZ area of ​​seam I is 38.17%.